2011
DOI: 10.1002/anie.201004101
|View full text |Cite
|
Sign up to set email alerts
|

Iron Catalysis for In Situ Regeneration of Oxidized Cofactors by Activation and Reduction of Molecular Oxygen: A Synthetic Metalloporphyrin as a Biomimetic NAD(P)H Oxidase

Abstract: An enzyme substitute: A synthetic FeIII porphyrin was used as a catalyst for the activation and reduction of O2 into H2O with the cofactor NAD(P)H in aqueous solution. The catalyst is compatible with different preparative enzymatic oxidation reactions. Thus, a new method is provided for the in situ regeneration of the oxidized cofactor NAD(P)+ with help from a non‐enzymatic, synthetic catalyst (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 27 publications
1
47
2
1
Order By: Relevance
“…Although there are several methods for in situ regeneration of NAD(P), including enzymatic, 1 chemical, 2 and electrochemical 3 regeneration, the high cost and low-stability of NAD(P) urge people to find out artificial cofactors which can replace and even surpass NAD(P). 4 NAD(P) contain two parts, the nicotinamide moiety acting as a hydride donor or acceptor and the adenine dinucleotide moiety playing an important role in separating between the anabolic and catabolic pathways.…”
mentioning
confidence: 99%
“…Although there are several methods for in situ regeneration of NAD(P), including enzymatic, 1 chemical, 2 and electrochemical 3 regeneration, the high cost and low-stability of NAD(P) urge people to find out artificial cofactors which can replace and even surpass NAD(P). 4 NAD(P) contain two parts, the nicotinamide moiety acting as a hydride donor or acceptor and the adenine dinucleotide moiety playing an important role in separating between the anabolic and catabolic pathways.…”
mentioning
confidence: 99%
“…-5 mmol (based on moles of metal atom), 0.05 M NaOH = 5 mL, P(O2) = 2.0 MPa, T= 433 K, and t= 2 h; b in 0.5 M H3PO4 aqueous solution; c in 0.5 M NaOH aqueous solution; d P(O2) = 0.6 MPa; e P(O2) = 1.0 MPa; f P(air) = 2 MPa Product analysis revealed that gluconic acid was the major oxidative product in the absence of a catalyst and that selectivity was up to 56%, as seen in Table 1, entry 1. Instead of gluconolactone, a primary product of TSPPFeCl-catalyzed oxidation of a glucose C-H bond with an in situ reduced coenzyme (Maid et al 2011), LWM acids were the main products in the present catalytic approach without a reductant. Furthermore, the product selectivity also depends noticeably on the temperature, O2 pressure, and the pH value of the reaction solution (Tables S1, S2, and S3 in the Appendix).…”
Section: Resultsmentioning
confidence: 97%
“…[18] In addition, very recently even the use of molecular oxygen as the oxidation agent of choice in combination with 1 as a catalyst was reported (see also next chapter about synthetic applications). [19][20][21] Although the mechanism and role of 1 in these specific applications has not been clarified in detail yet, for one of these applications it was postulated that a hydroperoxo species (with a comparable structure as 1 f shown in Scheme 6) is formed in situ. [20] Applications of FeTSPP (1) …”
Section: Structural Properties Of Fetspp (1) and Species Thereof In Wmentioning
confidence: 99%
“…[19][20][21] Although the mechanism and role of 1 in these specific applications has not been clarified in detail yet, for one of these applications it was postulated that a hydroperoxo species (with a comparable structure as 1 f shown in Scheme 6) is formed in situ. [20] Applications of FeTSPP (1) …”
Section: Structural Properties Of Fetspp (1) and Species Thereof In Wmentioning
confidence: 99%